Integrating Perspectives on Affective Neuroscience: Introduction to the Special Section on the Brain and Emotion. (July 2018) - Hamann, Stephan
In this special section, three target articles present three different perspectives on emotion and how it is implemented in the human brain. Fundamental issues are discussed such as the nature and organization of emotion's representation in the brain and the best approaches for elucidating emotion's neural basis. Comments and author replies further discuss these issues and explore their interconnections. A common theme of the target articles and commentaries is that multiple approaches and perspectives must be integrated across all levels of analysis to understand the neural basis of emotion.